2017
DOI: 10.1007/s00726-017-2513-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral treatment with a rattlesnake native polypeptide crotamine efficiently inhibits the tumor growth with no potential toxicity for the host animal and with suggestive positive effects on animal metabolic profile

Abstract: The efficacy of crotamine as antitumoral was first demonstrated by daily intraperitoneal (IP) injections of low doses of this toxin in an animal model bearing melanoma tumors. Significant inhibition of tumor growth and increased lifespan of mice bearing tumor was also noticed after 21 consecutive days of this daily IP administration of crotamine. However, due to the limited acceptance of treatments by IP route in clinical conditions, herein, we evaluated the antitumor effect of this native polypeptide employin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…We also hypothesize that the polysaccharide material that contacts the basement membrane of sarcolemma may also play a potential role in the effect observed for crotamine in skeletal muscle, as its affinity for proteoglycans present on cell membranes was largely studied and demonstrated by our group to explain the cytotoxic and antitumoral activity of crotamine [ 50 , 51 , 52 ]. In addition to its potential action on mitochondria, which are often numerous in striated skeletal muscle structure, the possible differential expression of proteoglycans in hind limbs and front paws skeletal muscles of an animal, may have equally the potential to explain the selective paralysis of mice hind limbs with no noticeable or important effects on mice front paws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also hypothesize that the polysaccharide material that contacts the basement membrane of sarcolemma may also play a potential role in the effect observed for crotamine in skeletal muscle, as its affinity for proteoglycans present on cell membranes was largely studied and demonstrated by our group to explain the cytotoxic and antitumoral activity of crotamine [ 50 , 51 , 52 ]. In addition to its potential action on mitochondria, which are often numerous in striated skeletal muscle structure, the possible differential expression of proteoglycans in hind limbs and front paws skeletal muscles of an animal, may have equally the potential to explain the selective paralysis of mice hind limbs with no noticeable or important effects on mice front paws.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we finished observing only total paralysis onset (data in S2 Video ), for any dose of crotamine evaluated, and the minimum concentration/doses of crotamine necessary for this effect could not be determined here. But at this point, it is important to consider that even after 21 days of daily ip treatment with crotamine (1 μg/animal, which correspond to about 0.04 mg/kg of BW), we have never observed the hind limbs paralysis or any other noticeable change in the general behavior of treated animals [ 50 , 52 , 63 ]. It is also worth to mention that the mice hind limbs paralysis was not observed up to 2 h after administration by oral route of a single dose of 200 μg of crotamine (which corresponds to about 8 mg/kg of BW), or after a long term daily treatment by oral gavage with crotamine (10 μg/animal, which correspond to about 0.04 mg/kg of BW) [ 52 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, natural compounds isolated from venomous animals have been less studied in this field, and an unexplored collection of molecules with potential to counteract obesity and ameliorate its complications remains unexplored. Previous observations that crotamine inhibits weight gain in animal models of melanoma 24 , 26 led us to explore the potential effects of crotamine on metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, another group has demonstrated the ability of crotamine to induce insulin secretion in cultured pancreatic beta cells 25 . In the present study, the main objective was to investigate the metabolic effects of crotamine in healthy wild-type mice after 21 days of oral treatment, which was demonstrated by our laboratory to be an effective protocol for crotamine as an antitumor treatment agent 26 . Here, we found that crotamine induces the differentiation of brown adipocytes and stimulates basal energy expenditure, thereby reducing adiposity and improving glucose homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…This toxin induces myonecrosis [24], paralysis and extension of hind legs, and spontaneous and irregular contractions in the diaphragm of rats, mice and rabbits [25] by acting on sodium and potassium channels [26,27]. More recently, it has been demonstrated that crotamine possesses antitumoral [28], cytotoxic [29], antibacterial [30][31][32], antileishmanial [33], anthelmintic [34] and antimalarial effects [35]; as well as induces platelet aggregation [32].…”
Section: Introductionmentioning
confidence: 99%